2017
DOI: 10.1016/j.amepre.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Softening Among U.S. Smokers With Psychological Distress: More Quit Attempts and Lower Consumption as Smoking Drops

Abstract: Introduction It has been argued that as smoking prevalence declines, the remaining smokers represent a “hard core” who are unwilling or unable to quit, a process known as hardening. However, as recently shown, the general smoking population is softening not hardening (i.e., as prevalence falls more quit attempts and lower consumption among continuing smokers). People with psychological distress smoke more, so they may represent hard core smokers. Methods Using cross-sectional time series analysis, in 2016–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
8
30
0
Order By: Relevance
“…Previous studies have shown that the relative risk of smoking associated with psychological distress has become stronger in the last 20 years, because the prevalence of smoking has declined more rapidly among those without psychological distress than among those with psychological distress [10][11][12][13][14] The current results suggest that other health behavior correlates of psychological distress have also changed during the last 10-20 years in the United States: psychological distress has become more strongly associated with physical inactivity and short sleep duration, but less strongly related with heavy alcohol consumption. The previously reported time trends of psychological distress and smoking suggest that the public health improvements have not reached people with mental health problems as effectively as those without mental health problems [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the relative risk of smoking associated with psychological distress has become stronger in the last 20 years, because the prevalence of smoking has declined more rapidly among those without psychological distress than among those with psychological distress [10][11][12][13][14] The current results suggest that other health behavior correlates of psychological distress have also changed during the last 10-20 years in the United States: psychological distress has become more strongly associated with physical inactivity and short sleep duration, but less strongly related with heavy alcohol consumption. The previously reported time trends of psychological distress and smoking suggest that the public health improvements have not reached people with mental health problems as effectively as those without mental health problems [10].…”
Section: Discussionmentioning
confidence: 99%
“…The total sample size was 603,518 participants (21,237-35,469 participants per survey year) aged 18 years and older. These data have previously been used to examine time period trends in psychological distress and smoking [11,13]. NHIS is approved by the Research Ethics Review Board of the National Center for Health Statistics and the U.S. Office of Management and Budget.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking is also associated with poorer treatment outcomes; compared with non-smokers with mental health problems, smokers with mental health problems spend longer time in hospital and less time out of hospital (11). There is some evidence, mainly from the US, that smokers with mental health problems are as likely to make a quit attempt as other smokers (12) but cessation rates are lower. Successful quitting is associated with improved mental health, speci cally reduced anxiety, depression and stress and increased psychological quality of life and positive affect (13); additionally, for speci c medications for severe mental illness, quitting may reduce the required dosage (5) and thus associated side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is also associated with poorer treatment outcomes; compared with nonsmokers with mental health problems, smokers spend longer time in hospital and less time out of hospital (11). There is some evidence, mainly from the US, that they are as likely to make a quit attempt than other smokers (12) but cessation rates are lower. Successful quitting is associated with improved mental health, specifically reduced anxiety, depression and stress and increased psychological quality of life and positive affect (13); additionally, for specific medications for severe mental illness, quitting may reduce the required dosage (5) and thus associated side effects.…”
Section: Introductionmentioning
confidence: 99%